Research trends from 1992 to 2022 of acupuncture anesthesia: a bibliometric analysis - Sun, Linxi; Wei, Xuqiang; Wang, Ke; Zhou, Jia (Frontiers in Medicine, 2023)
Background Acupuncture anesthesia is a significant technical development that originated in China in 1958 and was introduced to the West in the early 1970s. Due to its relative novelty, it has been the subject of intense scrutiny and contestation. Since the early 1970s, the use of acupuncture as a complementary treatment for opioid analgesics has been accepted. Research on acupuncture anesthesia has helped to reduce clinical opioid abuse. However, only a few articles have focused on previous publications that reflect the trend of the study, the main investigators, reciprocal collaboration, and other information in this field. In view of this, we utilized bibliographic analysis methods to objectively analyze current trends and research hotspots in this field, aiming to provide a foundation and reference for future studies. Methods The Web of Science database was searched for publications related to acupuncture anesthesia between 1992 and 2022. The CiteSpace and VOSviewer were used to analyze the annual publications, authors, Co-cited authors, and their countries (regions) and institutions, co-occurrence keywords, burst keywords, Co-citation references and Co-citation journals. Results A total of 746 eligible publications were retrieved from the database for the analysis, including 637 articles and 109 reviews. And the trend of annual publications continued to grow. Aashish J. Kumar, Daniel I. Sessler, Baoguo Wang, and Paul F. White published the most papers in this field (7), and all authors, had a very low centrality (<0.01). China (252) and the University of California System (21) were the most productive country (region) and institution, respectively, while the United States (0.62) and University of California System (0.16) had the highest centrality. After removing keywords related to the search strategy, the three most frequent were pain (115), electroacupuncture (109), and stimulation (91). The six most recent burst keywords were recovery, transcutaneous electrical acupoint stimulation, systematic review, quality, general anesthesia, and surgery. Wang et al.’s article had the highest co-citation count (20), whereas Zhang et al.’s articles had the highest centrality (0.25). The Journal of Anesthesia and Analgesia was the most influential one (408 co-citations). Conclusion This research provides valuable information for the study of acupuncture anesthesia. In recent years, frontier topics in acupuncture anesthesia research have been the promotion of perioperative rehabilitation, anesthesia management, and quality improvement.